Yak genetic resources of India: distribution, types and characteristics - BEHL, RAHUL; VIJ, P K; NIRANJAN, S K; JAYAKUMAR, S; BEHL, JYOTSNA; VIJH, R K (The Indian Journal of Animal Sciences, 2020)
In India, the yaks are reared by the people residing between 3,000 and 5,000 meters above mean sea level in the states of Jammu-Kashmir, Himachal Pradesh, Uttrakhand, Sikkim, Arunachal Pradesh and West Bengal. Yaks thrive well in these extremely cold regions with hypoxic conditions providing milk, meat, hide, fibre, manure and draught power to the local population. They are able to withstand the fodder scarcity endemic to these regions in the winter months. The total yak population in our country is 0.76 lakhs. Jammu and Kashmir has the maximum population of yak (0.54 lakh), possessing about 71% of the total yak population of the country, followed by Arunachal Pradesh (18.34%) and Sikkim (5.26%). The milk yield per lactation in indigenous yaks is 250–500 kg in a lactation period of 260–300 days. The birth weight of indigenous yaks in males and females is 14.20±0.33 and 13.20±0.34 kg, which increases to 201.23±4.79 and 178.13±3.26 kg, respectively, at 2 years of age. Mainly, four types of Indian yaks have been described namely Arunachali, Ladakhi, Sikkimi and Himachali. Out of these, Arunachali yaks are the first and only recognized breed of Indian yaks. This review summarizes the population trends, attributes of indigenous yaks in general as well of specific types of indigenous yaks available in India.